2004
DOI: 10.1007/s00264-004-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional treatment of closed humeral shaft fractures

Abstract: We treated 93 consecutive patients, average age 53 (16-90) years, with closed humeral shaft fractures applying a functional brace immediately after injury. Seventy-two (77%) fractures healed without problems. There were significantly more consolidation problems in fractures in the proximal third (46% consolidated) compared to those at the middle (81% consolidated) and distal third (86% consolidated) of the shaft. Logistic regression analysis revealed the only predictive factor in respect to successful brace tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 19 publications
2
63
1
6
Order By: Relevance
“…In contrast, nonunion is disabling because of pain and instability [6][7][8][9] . In prior studies, risk factors for nonunion were found to be open fractures, transverse mid-diaphyseal fractures (AO type A3), and spiral fractures (AO type A1) in the proximal part of the shaft 1,[10][11][12][13] . Sarmiento et al 1 observed a persistent gap between the fracture fragments in seven of sixteen patients with a nonunion after functional bracing of a humeral shaft fracture but did not quantify the risk of nonunion associated with a fracture gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, nonunion is disabling because of pain and instability [6][7][8][9] . In prior studies, risk factors for nonunion were found to be open fractures, transverse mid-diaphyseal fractures (AO type A3), and spiral fractures (AO type A1) in the proximal part of the shaft 1,[10][11][12][13] . Sarmiento et al 1 observed a persistent gap between the fracture fragments in seven of sixteen patients with a nonunion after functional bracing of a humeral shaft fracture but did not quantify the risk of nonunion associated with a fracture gap.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were (1) a closed fracture, (2) an AO type-A2 (oblique, ‡30°) or type-A3 (transverse, <30°) fracture, (3) a fracture in the middle third of the diaphysis, (4) no periprosthetic or peri-implant (nail or plate) fracture, (5) nonoperative treatment, and (6) either documented union (clinically and radiographically) two months or more after injury or a recommendation for surgery based on persistent motion between the fracture fragments and a persistent fracture line found on radiographs obtained six weeks or more after injury 13 . Of the eighty-two patients who fulfilled the inclusion criteria, three were excluded because they had had surgical treatment within three weeks after injury.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Rutgers and Ring retrospectively reviewed treatment of diaphyseal humerus fractures that were treated with functional bracing and found proximal third long oblique fractures may be at greater risk of nonunion (39 % in their study), they attribute this to the pull of the deltoid on the distal aspect of the proximal fragment and muscle interposition [9]. Toivanen et al also noted that over half of the fractures of the proximal third of the humerus in their study treated with functional bracing also went on to nonunion [17].…”
Section: Current Concepts In Nonoperative Versus Operative Interventionmentioning
confidence: 99%
“…Most of the fractures can be effectively treated conservatively [1,2]. Operative intervention is indicated in special circumstances including (1) failure of closed reduction, (2) intra-articular extension of fractures, (3) neurovascular compromises, (4) associated ipsilateral forearm and elbow fractures, (5) segmental fractures, (6) pathological fractures, (7) open fractures, (8) fractures in polytraumatised patients, (9) bilateral humeral shaft fractures, (10) periprosthetic fractures and (11) transverse or short oblique fractures [3].…”
Section: Introductionmentioning
confidence: 99%